HOW THE DISCOURSE OF SUFISM BECAME THE EXPRESSIVE DISCOURSE OF ISLAMIC RADICALISM IN THE REGIONS OF “POPULAR ISLAM” IN RUSSIA - KARABULATOVA, Irina; POLEKHINA, Maya; LYAUSHEVA, Svetlana; DUBININA, Natalia (CENTRAL ASIA AND THE CAUCASUS, 2017)
At the turn of the twenty-first century, the Caucasus became, once more in its history, the sphere of vital and strategic interests of Western and Eastern powers that placed a stake on separatist sentiments and Islamic forces. The importance of researching this issue is explained by the fact that radical Islam, which professes the idea of “pure Islam” (purified from the extraneous layers that built up over the course of history), made the ideas of Wahhabism easily grasped and, therefore, willingly embraced, making regional communicative practices very distinctive. Salafism in its neo-Wahhabi garbs opposes the region’s traditionalism. Given the vehement conflicts unfolding between groups of Muslim clerics and their followers in Daghestan, the already familiar antagonism between the traditionalists (followers of three Sufi tariqats) and fundamentalists (conventional definition of those who believe that Islam should be returned to the times of the Prophet Muhammad) was further intensified by the contradictions between spiritual leaders, each of whom represented specific ethnic groups. The communicative register is not relevant to the conflict discourse of extremism and/or terrorism, while any communicative failure may reveal its constructive potential if those involved in the discourse, which may unfold according to any scenario, are not afraid to define the situation. It was in the wake of the Chechen wars that the radical Islamic movement in the Northern Caucasus acquired specific organizational forms. The wars served as a catalyst for the Wahhabi movement in Daghestan and were responsible for the gradual emergence of a highly specific discourse of radicalism, the product of transformation of the traditional Sufi discourse as one of the common features of “popular Islam.” It was at that time that the neo-Wahhabi discourse acquired predominantly extremist features, which is especially apparent in the digital format. The systemic crisis transformed the idea of Imarat Kavkaz into the only force that offered its own model of unification of the Caucasus. The idea of pure Islam was willingly embraced by the local Muslims, first and foremost the younger generation, which became cannon fodder for the leaders of Imarat and the sluggish civil war underway in Daghestan.